2016
DOI: 10.1038/srep24310
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of mutation profiling in patients with stage II and III colon cancer

Abstract: Development of colorectal cancer (CRC) associates with accumulation of genetic mutations include the epidermal growth factor receptor (EGFR) signaling pathway. However, whether mutations in KRAS together with downstream factors BRAF, PIK3CA and NRAS impact prognosis is still unclear for stage II-III colon cancer. In the present study a total of 228 stage II-III colon cancer samples were retrospectively collected, KRAS (codons 12, 13 and 61), BRAF (exon 11 and exon 15), PIK3CA (exon 9 and exon 20) and NRAS (cod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 40 publications
(76 reference statements)
5
21
0
4
Order By: Relevance
“…Although a substantial amount of data has been reported on KRAS gene mutations, relative little data has been reported on NRAS mutations. In the present study, NRAS mutations were detected in 1.9% of tumors compared with 4.3% from Taiwan (Chang et al, 2016), 0.9-4.2% from China (Shen et al, 2013;Zhang et al, 2015;Shen et al 2016), 2.7-4.5% from Japan (Ogura et al, 2014;Kawazoe et al, 2015;Osumi et al, 2016), 2.3% from Korea (Lee et al 2015), 3.6-4.6% from Italy (Foltran et al, 2015;Malapelle et al, 2016), and 2.2-5.1% from the United States (Irahara et al, 2010;Vaughn et al, 2011).…”
Section: Discussionmentioning
confidence: 42%
“…Although a substantial amount of data has been reported on KRAS gene mutations, relative little data has been reported on NRAS mutations. In the present study, NRAS mutations were detected in 1.9% of tumors compared with 4.3% from Taiwan (Chang et al, 2016), 0.9-4.2% from China (Shen et al, 2013;Zhang et al, 2015;Shen et al 2016), 2.7-4.5% from Japan (Ogura et al, 2014;Kawazoe et al, 2015;Osumi et al, 2016), 2.3% from Korea (Lee et al 2015), 3.6-4.6% from Italy (Foltran et al, 2015;Malapelle et al, 2016), and 2.2-5.1% from the United States (Irahara et al, 2010;Vaughn et al, 2011).…”
Section: Discussionmentioning
confidence: 42%
“…But in early stage CRC patients, the prognostic role of BRAF mutations is controversial (Gallo et al, 2019;Smeby et al, 2018). A study conducted by European scholars showed BRAF mutation was an independent prognostic factor in stage II and III CRC (Fariña-Sarasqueta et al, 2010), and a meta-analysis based on randomized clinical trials showed BRAF mutation patients presented poor response to adjuvant chemotherapy (Zhu et al, 2016); however, Chinese scholars demonstrated BRAF mutation did not have prognostic value in stage II and III CRC patients (Shen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Мутации гена PIK3CA (каталитическая субъединица PI3K) присутствуют в 10-20 % всех случаев КРР, чаще проксимальной локализации [22]. Оценить прогностическую роль изолированной мутации PIK3CA трудно, так как до 50 % опухолей несут также мутации BRAF и еще 40 % имеют сопутствующую мутацию RAS [23,24].…”
Section: генетика колоректального ракаunclassified